CONFLICT OF NORM ANTARA PENCABUTAN HAK DAN PENITIPAN GANTI KERUGIAN DI PENGADILAN DALAM PENYELESAIAN SENGKETA PENGADAAN TANAH UNTUK PEMBANGUNAN - M. Hamidi Masykur; Harinanto Sugiono (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
Article 18 of Law No. 5 of 1960 concerning Basic Rules of Agrarian states that “For the public interest, including the national and State interest also the peoples interest, land rights may be revoked with reasonable compensation in accordance to the procedure provided by law.” The phrase of “revoked” in the article can be widely interpreted both in terms of the procedure as well as the authority. A year after the enactment of Law No. 5 of 1960, Law No. 20 of 1961 concerning Revocation of Land Rights and Properties on Land was enacted with the purpose to implement Article 18 of Law No. 5 of 1960. According to Law No. 20 of 1961, revocation of land rights for the public interests can be exercised through Presidential Decree. It means that there is no opportunity for the lands owner to ﬁle an objection against the revocation. On the other side, the enactment of Law No. 2 of 2012 concerning Land Procurement for Development in which Article 40 of the Law provides the custody mechanism for compensation to the District Court when the lands owner refuse to accept the compensation. The procedure has been conﬁ  rmed by Supreme Court, which enacted Supreme Court Regulation No. 3 of 2016 concerning the Procedure for Submitting Objection and Compensation Custody to the District Court in Land Procurement for Public Interests. This situation shows conﬂ  ict of norms between Law No. 20 of 1961 which is never declared not applicable, and then Law No. 2 of 2012 was enacted as new law in the same ﬁeld of regulation.